Durability consideration of foamed concrete - Tan, K.E (Universiti Malaysia Sarawak, UNIMAS, 2009)
Foamed concrete is a concrete which contains a lot of artificial pore distributed throughout the mass of concrete. The main purpose of the artificial pores is to reduce the density and weight of concrete. This study is mainly focused on water absorption and capillary sorption which two main factors are influencing the durability of foamed concrete. Durability of concrete is the ability to resist the deterioration process. Several mix proportions were applied to produce the tested specimens; specimens from low density (730 kg/m3 ) to moderate density (1270 kg/m3 ) and specimens with and without replacement of sand by fly ash are considered. The tests showed that low density foamed concrete absorbed more water. For the same density, specimens containing fly ash absorbed less water for both water absorption and capillary sorption. Capillary sorption test showed that artificial pores contributed in the capillary action to take in water. Compare to capillary sorption, water absorption is higher because of the larger surface contact between water and concrete surface. Foamed concretes with 28 days of age showed that increasing in ingredient of fly ash in the mixtures reduced its compressive strength